Multifunctional Compound‐Regulated SnO2 for High‐Efficiency and Stable Perovskite Solar Cells under Ambient Air. Issue 2 (22nd January 2022) - Qiu, Linlin; Chen, Liang; Chen, Wei‐Hsiang; Yuan, Yongfeng; Song, Lixin; Mei, Deqiang; Bai, Bing; Xie, Fuqiang; Du, Pingfan; Xiong, Jie
Abstract: Perovskite solar cells (PSCs) fabricated with a low‐temperature (≤150 °C) SnO2 ‐based electron transport layer (ETL) have been rapidly developing and demonstrate high power conversion efficiency (PCE). To further enhance the efficiency and stability of PSCs, high‐quality perovskite and SnO2 films are needed, and the interfacial performance between the SnO2 ETL and the perovskite layer needs to be improved. In this work, potassium p ‐aminobenzoate (KPAB) was introduced to regulate the SnO2 ETL to obtain reduced defects and an excellent wetting property, inducing vertically aligned crystal growth of the perovskites on the interface side of the SnO2 ETL. In addition, the potassium ions were able to interact with the halogen ions of the perovskite, which further enhanced the quality of the perovskite film. Due to the abovementioned strengths of KPAB, we demonstrated that devices based on KPAB‐SnO2 have a higher power conversion efficiency (19.03 %), better reproducibility, and superior operational stability compared to devices with pristine SnO2 . Abstract : The potassium p– aminobenzoate (KPAB) was used to optimize the SnO2 ETL. −NH2 in KPAB can coordinate with Pb of perovskite to reduce defect density. −COO − in KPAB can adsorb on the surface of SnO2 . Therefore, KPAB help form a chemical bridge between the SnO2 and perovskite layers. In addition, the potassium ions are able to interact with halogen ions of perovskite, thereby effectively reducing defect states, suppressing hysteresis and enhancing PSCs performance and stability.